Risk‐based water resources planning in practice: a blueprint for the water industry in England. (12th April 2019) - Hall, Jim W.; Mortazavi‐Naeini, Mohammad; Borgomeo, Edoardo; Baker, Bill; Gavin, Helen; Gough, Meyrick; Harou, Julien J.; Hunt, Douglas; Lambert, Chris; Piper, Ben; Richardson, Nathan; Watts, Glenn
Abstract: Resilient water supplies in England need to be secured in the face of challenges of population growth, climate change and environmental sustainability. We propose a blueprint for water resources planning that uses system simulation modelling to estimate the frequency, duration and severity of water shortages at present and in the context of future plans and scenarios. We use multiobjective optimisation tools to explore trade‐offs between these risk metrics and cost of alternative plans, and we use sensitivity analysis to identify plans that robustly achieve targets for tolerable risk, alongside other performance objectives. The results of a case study in the Thames basin demonstrate that the proposed methodology is feasible given commonly available data sets and models. The proposed method provides evidence with which to develop water resource management plans that demonstrably balance the risks of water shortages, costs to water users and environmental constraints in an uncertain future.